1988
DOI: 10.3109/00016488809106441
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament proteins in spindle cell carcinoma of the larynx and tongue

Abstract: In an analysis of intermediate filament protein expression of spindle cell carcinoma, a variant of squamous cell carcinoma, occurring in larynx and tongue, vimentin positivity was found in sarcomatoid areas in 12 of 13 patients. Scattered expression of keratin was observed in sarcomatoid areas in tumours of 10 patients. However, large parts of sarcomatoid areas of such tumours were negative for keratin. Overlying dysplastic epithelium and squamous cell carcinoma components were positive for keratin. In a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
4
10
0
1
Order By: Relevance
“…The degree and intensity of epithelial marker expression is also reported to vary [3] as was observed in our study as well. Immunopositivity with any of the epithelial markers was observed in 53.4% of cases in our study, comparable to reported figures of between 48 and 75% [3,17,19,23,[25][26][27]. This may be due to a number of technical and histological factors as detailed by Thompson et al [3] which include subjectivity in interpretation, sampling error, nonhomogeneous tumors, poor preservation or fixation, inappropriate antibody or technique, or epithelial features less than the threshold of detection.…”
Section: Histomorphologysupporting
confidence: 80%
See 4 more Smart Citations
“…The degree and intensity of epithelial marker expression is also reported to vary [3] as was observed in our study as well. Immunopositivity with any of the epithelial markers was observed in 53.4% of cases in our study, comparable to reported figures of between 48 and 75% [3,17,19,23,[25][26][27]. This may be due to a number of technical and histological factors as detailed by Thompson et al [3] which include subjectivity in interpretation, sampling error, nonhomogeneous tumors, poor preservation or fixation, inappropriate antibody or technique, or epithelial features less than the threshold of detection.…”
Section: Histomorphologysupporting
confidence: 80%
“…Sarcomatoid carcinoma contains both a conventional epithelial squamous component and a sarcomatous spindle cell component [2,3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. As also noted in our study, epithelial differentiation evident within the tumor is reported to be highly variable with either changes in the overlying epithelium in the form of dysplasia or carcinoma in situ or as part of the infiltrating tumor [1][2][3].…”
Section: Histomorphologysupporting
confidence: 56%
See 3 more Smart Citations